2017
DOI: 10.1007/s12325-017-0626-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Once-Daily Umeclidinium/Vilanterol and Tiotropium/Olodaterol Therapy in Symptomatic Chronic Obstructive Pulmonary Disease: A Randomized Study

Abstract: IntroductionWe report the results of the first direct comparison of the once-daily fixed-dose long-acting muscarinic antagonist/long-acting β2-agonist (LAMA/LABA) combinations umeclidinium/vilanterol (UMEC/VI) and tiotropium/olodaterol (TIO/OLO) in patients with COPD.MethodsThis was a randomized, two-period crossover open-label study in symptomatic patients with COPD [age 40 years or older, postbronchodilator forced expiratory volume in 1 s (FEV1) of 70% or less and 50% or more of predicted normal values, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
116
2
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(137 citation statements)
references
References 40 publications
7
116
2
12
Order By: Relevance
“…This was a post hoc analysis of an 8-week, multicenter, randomized, open-label, two-period crossover study (NCT02799784; GSK clinical study identifier 204990) conducted in centers across Germany, Spain, UK, and the USA between July 2016 and April 2017 [21]. The objective of the current analysis was to evaluate the efficacy and safety of UMEC/VI versus TIO/ OLO in an unexpectedly large subgroup of patients who were initiated on a COPD maintenance therapy at randomization.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This was a post hoc analysis of an 8-week, multicenter, randomized, open-label, two-period crossover study (NCT02799784; GSK clinical study identifier 204990) conducted in centers across Germany, Spain, UK, and the USA between July 2016 and April 2017 [21]. The objective of the current analysis was to evaluate the efficacy and safety of UMEC/VI versus TIO/ OLO in an unexpectedly large subgroup of patients who were initiated on a COPD maintenance therapy at randomization.…”
Section: Methodsmentioning
confidence: 99%
“…Eligibility criteria for enrollment in the study have been previously reported [21]. In brief, patients were C 40 years of age with a diagnosis of COPD in accordance with the American Thoracic Society/European Respiratory Society (ATS/ERS) definition [29]; current or former smokers with a smoking history of C 10 packyears; had a pre-and post-bronchodilator FEV 1 /forced vital capacity (FVC) ratio \ 0.70 and a post-bronchodilator FEV 1 B 70% and C 50% of predicted normal values at enrollment (visit 1) [30]; and had a score of C 2 on the modified Medical Research Council Dyspnea Scale (mMRC) [31].…”
Section: Patientsmentioning
confidence: 99%
See 3 more Smart Citations